2011
DOI: 10.2106/jbjs.i.01557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amputation Level on Energy Expenditure During Overground Walking by Children with an Amputation

Abstract: Children with an amputation through the knee or distal to the knee were able to maintain a normal walking speed without significantly increasing their energy cost. Only when the amputation is above the knee do children walk significantly slower and with an increased energy cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…28 Thus, amputation may not unavoidably increase the cost of walking and pre-amputation metabolic costs of walking may be achieved with passive prostheses. Similar findings of equivalent metabolic costs between individuals with and without TTA when walking at the same speed occur infrequently in the literature but have been reported in children with traumatic amputations or congenital limb absences 29,30 and other cohorts of Service Members. 12 Although the equivalent metabolic costs between individuals with TTA and controls were promising, it was not expected that individuals with more proximal amputations (e.g.…”
Section: Introductionsupporting
confidence: 82%
“…28 Thus, amputation may not unavoidably increase the cost of walking and pre-amputation metabolic costs of walking may be achieved with passive prostheses. Similar findings of equivalent metabolic costs between individuals with and without TTA when walking at the same speed occur infrequently in the literature but have been reported in children with traumatic amputations or congenital limb absences 29,30 and other cohorts of Service Members. 12 Although the equivalent metabolic costs between individuals with TTA and controls were promising, it was not expected that individuals with more proximal amputations (e.g.…”
Section: Introductionsupporting
confidence: 82%
“…The level of lower extremity amputation is directly proportional to the increase in oxygen consumption required for ambulation. 2,3 Retrospective studies found a wide range, from 5% to 61%, of either the ipsilateral or contralateral hip osteoarthritis after a lower extremity amputation. 4,5 Kulkarni et al 5 retrospectively evaluated 44 lower extremity amputees and found that 24 (55%) of the ipsilateral hips and 8 (18%) of the contralateral hips had osteoarthritis.…”
mentioning
confidence: 99%
“…6 Although these functional results are sobering, it needs to be borne in mind that disarticulation of the hip is a major undertaking with a significant associated mortality rate 16,17 Disarticulation is difficult to manage with a prosthesis, which is cumbersome and physically demanding. 18 In addition, Chin et al 19 have shown that the mobilisation of elderly patients following disarticulation of the hip is very limited, and that wheelchair use represented an alternative and realistic goal. There may also be significant psychological sequelae.…”
Section: Discussionmentioning
confidence: 99%